AN INVESTIGATION OF THE EFFECTIVENESS OF FLIPPED CLASSROOM TEACHING IN PROJECT MANAGEMENT COURSE: A CASE STUDY OF AUSTRALIAN HIGHER EDUCATION - Khanal, Rakesh (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This paper is a pedagogical experimental study which describes a trial of a flipped-classroom approach of teaching within the context of project management education to a cohort of international students. Project management being an applied course cannot be learned entirely thorough a textbook under traditional teaching setting. Therefore, a flipped-classroom approach has been introduced to address the need to transform the traditional teaching pedagogy to foster active learning in project management education. The flipped classroom model adopted in the present paper has three important components: offloaded content made available through an online learning management system, student-centred in-class activities and three major assessments. The result of factor analysis revealed that pre-class activity has a greater role to play in the success of a flipped class. The result of the study further shows that the flipped-classroom approach is effective in enhancing student’s performance in terms of the final grade and overall student learning experience. Also, the results show that flipped classroom approach led to a significant increase in student performance on average as compared to the traditional lecture-based approach suggesting that the flipped classroom approach is a good substitute to traditional lecture-based teaching for an applied course such as project management. More importantly, flipped classroom teaching could serve as a good tool for Emergency Remote Learning (ERL) to substitute Face-to-Face teaching amidst the COVID-19 pandemic.